Effectiveness of Project-Based and Case-Based Learning Models on Children's Numeracy Literacy Skills in Schools - Safira, Ifa; Yastanti, Unpris; Walid, Abul; Santosa, Tomi Apra; Sukini, Sukini; Safar, Muh; Solissa, Everhard Markiano; Wantu, Hasyim Mahmud (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
There are many studies on project-based learning and case-based learning models in the world of Education, but many studies have concluded that the results of the research are different and the influence of the model is not profound on Children's numeracy skills. This study aims to determine the effectiveness of project-based and case-based learning models to improve Children's numeracy literacy skills in schools. The type of research is quantitative research with a meta-analysis approach. The eligibility criteria of this study are that the research must be relevant, the research data is obtained from the ScienceDirect database; Mendeley; ERIC and Google Scholar; The research was published in 2020-2025; and The research must report complete data to calculate the effect size value. Data analysis with the help of Excel and Jamovi applications to calculate the effect size value of each study. The results of the study concluded that the 19 studies analyzed obtained a summary effect size value (d = 0.924; z = 7.446 p < 0.001). These findings show that the project-based learning and case-based learning models have a significant influence on Children' numeracy literacy skills in schools.